Effects of job enlargement on job satisfaction in Moshi district council - Msofe, Hadija M. (mzumbe University, 2024)
A dissertation submitted to School of Public Administration and Management (SOPAM) in partial fulfillment for the requirement of an award of Masters of Social Science in Human Resource Management (Msc. HRM) of Mzumbe University